2019
DOI: 10.1016/j.cppeds.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to PCBs and neurological and sexual/pubertal development from birth to adolescence

Abstract: Several chemical compounds are resistant to degradation and end up in the food chain. One group of these chemicals is polychlorinated biphenyls (PCBs) which are used as flame retardants and plasticizers. Although PCBs were banned several decades ago, PCBs are still found in environmental media, including in the body of humans. PCBs are transferred from mother to fetus via the placenta during pregnancy. Considering that the prenatal period is a sensitive period during which essential developmental processes tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 97 publications
0
12
2
Order By: Relevance
“…The frame of the continuous performance test of the NES3 was used to develop a test which might be feasible for 3 year old children. We noticed that most children didn't complete [2]. In contrast to others, we didn't find any influence of breastfeeding [53][54][55].…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The frame of the continuous performance test of the NES3 was used to develop a test which might be feasible for 3 year old children. We noticed that most children didn't complete [2]. In contrast to others, we didn't find any influence of breastfeeding [53][54][55].…”
Section: Discussioncontrasting
confidence: 65%
“…parental smoking [47]. Effects on temperament related to PCBs or dioxinlike compounds have not been frequently reported in toddlers [2]. Our results reported in Table 6.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Quite a bit is known about interactions between age and environmental factors of endocrine disruption per se [ 38 40 ]. Many studies have found that earlier exposure in the perinatal period leads to the greatest alterations in behavior and physiology [ 41 , 42 ]. This early period is characterized with vulnerable physiological and anatomical development including brain regions involved in cognition, emotion and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PCBs interfere with the function of various neurotransmitters such as dopamine, norepinephrine, and serotonin, affecting brain function (Mariussen & Fonnum 2003). Other studies show an association between exposure to PCBs and motor and cognitive delay in infants (Berghuis & Roze 2019). This would be closely related to the powerful interaction of PCBs with thyroid hormones (Prezioso et al 2018); these displace thyroxine from its carrier protein, fetal transthyretin, allows thyroid hormone to enter the fetal brain, thus having the potential to alter normal brain development (Miller-Pérez et al 2009).…”
mentioning
confidence: 99%